Pengaruh Panjang Potongan Entres dan Aplikasi Zpt Dari Ekstrak Bawang Merah (Allium Cepa L.) Terhadap Keberhasilan Teknik Sambung (Grafting) Kakao (Theobroma Cacao L.) - Wunto, Arby Okriansa; Murdono, Djoko (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the effect of scion length on the success of cocoa top grafting, the effect of the number of scion buds on grafting success, and the effect of shallot extract on the success of cocoa top grafting. Data collection in this study was carried out using a Randomized Block Design (RBD) with 7 treatments and 4 replications. The data samples were analyzed using Analysis of Variance (ANOVA), followed by the Honestly Significant Difference (HSD) test. The HSD test was conducted to determine which treatment means were significantly different and which were not. It was found that treatment P3 involving 4 scion buds and 300 ml/liter of shallot extract resulted in the highest survival rate of 100% and produced optimal growth responses across all observed parameters, including shoot length, number of leaves, growth rate, and stem diameter (both upper and lower stem). The effects of scion length and the application of growth regulators (PGR) from shallot extract on the parameters of shoot length and stem diameter (upper and lower) did not show significant differences, while the number of leaves and growth rate parameters showed significant effects. The treatment that produced the highest survival rate of 100% and showed optimal growth responses across all observed parameters was the treatment with 4 scion buds and 300 ml/liter of shallot extract (Treatment P3).